Peptide-Based Rapid and Selective Detection of Mercury in Aqueous Samples with Micro-Volume Glass Capillary Fluorometer - Marta Sosnowska; Emil Pitula; Monika Janik; Piotr Bruździak; Mateusz Śmietana; Marcin Olszewski; Dawid Nidzworski; Beata Gromadzka (Biosensors)
Mercury, a toxic heavy metal produced through both natural and anthropogenic processes, is found in all of Earth’s major systems. Mercury’s bioaccumulation characteristics in the human body have a significant impact on the liver, kidneys, brain, and muscles. In order to detect Hg2+ ions, a highly sensitive and specific fluorescent biosensor has been developed using a novel, modified seven amino acid peptide, FY7. The tyrosine ring in the FY7 peptide sequence forms a 2:1 complex with Hg2+ ions that are present in the water-based sample. As a result, the peptide’s fluorescence emission decreases with higher concentrations of Hg2+. The FY7 peptide’s performance was tested in the presence of Hg2+ ions and other metal ions, revealing its sensitivity and stability despite high concentrations. Conformational changes to the FY7 structure were confirmed by FTIR studies. Simultaneously, we designed a miniaturized setup to support an in-house-developed micro-volume capillary container for volume fluorometry measurements. We compared and verified the results from the micro-volume system with those from the commercial setup. The micro-volume capillary system accommodated only 2.9 µL of sample volume, allowing for rapid, sensitive, and selective detection of toxic mercury (II) ions as low as 0.02 µM.